Proceedings of the 2nd International Conference on Intervention and Applied Psychology (ICIAP 2018) 2019
DOI: 10.2991/iciap-18.2019.64
|View full text |Cite
|
Sign up to set email alerts
|

Counterproductive Work Behavior Among Government Employees: The Role of Basic Psychological Needs, Compensation, and Organizational Justice

Abstract: This study examined the mediating role of perceived organizational justice (procedural, interpersonal, and distributive justice) dimensions in explaining the association between basic psychological needs (need for autonomy, competence, and relatedness), compensation, and counterproductive work behavior (CWB). The participants in this study were 277 employees from various government institutions (local government, ministries, and boards). Data were collected through convenience sampling and tested using Hayes's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…It has been demonstrated that leadership is a critical component of work behavior because leaders direct, inspire, create a positive work environment, and influence innovative work behavior (Lee, Legood, Hughes, Tian, Newman, & Knight, 2020). Previous studies have shown that the negative work behavior of employees becomes a problem in organizations around the world which results in financial losses, reduces performance, and harms the organization's reputation (Pratama & Parahyanti, 2018;Van Steijn, Scheepstra, Yasar, Olff, De Vries, & Van Pampus, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that leadership is a critical component of work behavior because leaders direct, inspire, create a positive work environment, and influence innovative work behavior (Lee, Legood, Hughes, Tian, Newman, & Knight, 2020). Previous studies have shown that the negative work behavior of employees becomes a problem in organizations around the world which results in financial losses, reduces performance, and harms the organization's reputation (Pratama & Parahyanti, 2018;Van Steijn, Scheepstra, Yasar, Olff, De Vries, & Van Pampus, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…DTP officials influenced by the poor perception of the organizational distributive justice (ODJ), organizational interaction justice (OIJ) and organizational procedural justice (OPJ.) are more likely to indulge themselves in CWB (Bilal et al , 2019; Pratama and Parahyanti, 2019). This interaction of DTP traits and situational factors such as organizational related to CWB may add to the literature attempting to overcome or avoid the factors causing these negative behaviors (Baka, 2018) because, according to the principle of social exchange theory (SET), work misbehaviours seem to be a viable consequence for negative outcomes (Blau, 1964).…”
Section: Introductionmentioning
confidence: 99%
“…organizational justice, is considered in the study, which is likely to mediate the relationship because personality traits are affected by the individual’s justice perception, as suggested by researchers. Researches indicate that all these three dimensions of organizational justice are distinct from each other (Bilal et al , 2019; Pratama and Parahyanti, 2019). Few studies investigated the relationship between justice and negative workplace behaviors (Bilal et al , 2019; Priesemuth et al , 2013; Pratama and Parahyanti, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation